Pengaruh Pembelajaran Online Berbasis Zoom Cloud Meeting dan Google Classroom Terhadap Hasil Belajar - Prima Sadewa; Riska Damayanti (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2022)
The research has a goal, namely 1) Knowing the effect of learning with zoom cloud meetings on learning outcomes. 2) Knowing the effect of learning with google classroom has an impact on learning outcomes. 3) The effect of learning with zoom cloud meeting and google classroom together has an impact on the learning outcomes of inferential statistics for undergraduate accounting students at Pamulang University. A quantitative approach with associative type is used in this study. Methods of collecting research data with questionnaires and documentation. Test the validity and reliability for the instrument, test prerequisites before analysis, and test the hypothesis with regression. This study obtained the following results: (1) Online learning with zoom cloud meeting has an impact on learning outcomes, (2) online learning with google classroom has an impact on learning outcomes, (3) online learning with zoom cloud meeting and google classroom jointly have an impact on the learning outcomes of inferential statistics students of S1 Accounting at Pamulang University.Keywords: Zoom; Google Classroom; Learning Outcomes.